2021
DOI: 10.53562/ajcb.aqoe1932
|View full text |Cite
|
Sign up to set email alerts
|

Size Matters: First record of minimum male size at maturity and mating of free-ranging, endangered Indian Python Python molurus

Abstract: Indian python Python molurus (Linnaeus, 1758) is one of the world’s giant snakes with maximum lengths measured six to eight meters. Nevertheless, information on the size at maturity of P. molurus is not available. On February 9, 2019, 12:56 pm, one female and two males were observed during the group mating in Moyar River Valley Landscape, Southern India. We report the first observation on smallest male measuring 198 cm total length, 172 cm snoutvent length and weighing 3.3.kg mated with a radio-tagged larger f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In the native range, the smallest reproductive male of the closely related Indian python measured 172 cm SVL (198 TL;Vishnu et al 2021). Small mature male Burmese pythons have been documented in breeding aggregations in Florida (168 cm SVL, 193 cm TL;Smith et al 2015) and thus far, the smallest sexually mature male has measured only 125 cm SVL (143 cm TL, Currylow et al 2022b, c).…”
Section: Size At Maturitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the native range, the smallest reproductive male of the closely related Indian python measured 172 cm SVL (198 TL;Vishnu et al 2021). Small mature male Burmese pythons have been documented in breeding aggregations in Florida (168 cm SVL, 193 cm TL;Smith et al 2015) and thus far, the smallest sexually mature male has measured only 125 cm SVL (143 cm TL, Currylow et al 2022b, c).…”
Section: Size At Maturitymentioning
confidence: 99%
“…These data gaps may impede efforts to evaluate any applied genetic biocontrol tools and likewise prevent comprehensive understanding of how many biologically manipulated individuals would need to be released on the landscape to yield population declines. Recent and active progress is being made by USGS and others to fill these data gaps on life history knowledge (e.g., Soto-Shoender et al 2020;Bartoszek et al 2021b;Pittman and Bartoszek 2021;Taillie et al 2021;Vishnu et al 2021;Whitney et al 2021;Anderson et al 2022;Currylow et al 2022b).…”
Section: Demography and Genetic Biocontrolmentioning
confidence: 99%
“…229 cm total length vs. 259 cm total length reported by Pope 1961). There are no other known records of verified minimum size at maturity in wild male Burmese pythons with the closest relative, the Indian python (P. m. molurus), only very recently reported from the native range to be 172 cm SVL (198 total length; Vishnu et al 2021). Likewise in females, a single prior report noted that the smallest reproductive female Burmese python known was found in May 2013 from the southern Florida population and reached only 210 cm total length with 11 oviductal eggs (Willson et al 2014), and, very recently, another female of this size was reported to be gravid from the same population (Anderson et al 2022).…”
Section: Size At Maturitymentioning
confidence: 99%